1129. Optimizing Feedback Strategies on the Infectious Diseases Inpatient Service. (31st December 2020) - Clark, Eva; Kulkarni, Prathit; Mohajer, Mayar Al; Rose, Stacey; Serpa, Jose; Singhal, Geeta; Giordano, Thomas Giordano
Abstract: Background: Timely, efficient, and effective feedback strategies are crucial for enhancing faculty-trainee communication and trainee education. Here we describe attitudes, practices, and perceived behaviors regarding giving feedback to medical trainees rotating on Infectious Diseases (ID) inpatient consult services. Methods: An anonymous survey on feedback strategies was distributed to our adult ID Section in February 2020 as part of a facilitated discussion on optimizing trainee clinical education. Results: Twenty-six ID Section members completed the survey (18 faculty, 8 trainees). Most trainees (62.5%) and faculty (66.7%) felt that trainees are "sometimes" comfortable voicing concerns to faculty; however, no trainees but 11.1% of faculty indicated that trainees are "always" comfortable voicing concerns to faculty. Most trainees (87.5%) felt that conversations about team expectations occur "sometimes" or "often." In contrast, most faculty (72.2%) felt that these conversations "always" occur. Although most faculty felt that both informal (94.4%) and formal (83.3%) feedback should be given to trainees, 22.2% of faculty responded that they do not explicitly use the term "feedback" when discussing feedback with a trainee. No trainees and 22.2% of faculty indicated that they utilize a feedback tool. Regarding quantity of feedback trainees perceive they receive from faculty, 37.5% of trainees felt they needed more feedback while 50% felt they received adequate feedback. Most faculty (88.9%) responded that they encourage trainees to give feedback to faculty, although most trainees (62.5%) responded "sometimes" regarding how comfortable they feel doing so. Conclusion: In summary, we found differences between faculty and trainees regarding two important aspects of medical education: setting expectations and providing feedback. While most faculty feel that conversations regarding these topics occur invariably, trainees do not always share this perception. Trainees felt less comfortable voicing concerns and giving feedback to faculty than faculty perceived them to be. Overall, the data suggest that there is room for improvement to ensure that trainees and faculty are operating from a shared mental model regarding setting team expectations and providing/receiving feedback. Disclosures: All Authors : No reported disclosures